The role of academic supervision in improving teacher professionalism - Tidjani, Afifah; Lailiyah, Zulfiyatul (Educenter : Jurnal Ilmiah Pendidikan, 2023)
The role of academic supervision is very important to be held by an educational institution in improving the quality of teacher teaching and to achieve the goals that have been set. The quality of teacher teaching greatly affects the quality of a child's achievement. The purpose of this study is to determine the implementation of academic supervision as well as the supporting and inhibiting factors of academic supervision activities. The method used is a case study with a qualitative approach. The results of this study indicate that the implementation of academic supervision is carried out in three stages, namely: Conducting class visits every lesson hour conducted by each supervisor who has a supervision schedule, coaching teachers who have problems in teaching, evaluating the results of the supervisor's report. Supporting factors in the implementation of academic supervision are the role of the principal in motivating teachers who have problems in teaching, and facilities in the form of supervisor files. The large number of classes and the minimal number of supervisors make this academic supervision activity less than optimal. Because the supervisors themselves experience problems in visiting the classes to be supervised.